OC-028 Small Bowel Cancer In The Uk. (9th June 2014) - Chan, L; Evans, G
Abstract : Introduction: Small bowel cancer (SBC) is uncommon worldwide and accounts for only 5% of all gastrointestinal (GI) malignancies despite the small bowel forming 75% of the GI tract. [1] Our understanding is limited by its rarity, insidious course, difficult assessment and late diagnosis, coupled with multiple histological subtypes. We aim to review the trend of SBC in the UK over the last two decades. Methods: The national UK Association of Cancer Registries (UKACR) database identified SBC patients diagnosed from January 1991 to January 2009. We retrospectively reviewed and carried out a descriptive analysis of SBC incidence rates with respect to gender, age, ethnicity (as per UK Census 2001) and socio-economic status (as per UK Indices of Deprivation 2004, 2007 and 2010) and mortality rates. Results: The registry identified 11, 872 patients, 53.6% male and 46.4% female, who were diagnosed at a singular peak mean age of 67 years over the study period. The overall incidence of SBC increased from 0.71 to 1.51 per 100, 000 from 1991 to 2009 with mortality increasing simultaneously but to a lesser extent (Figure 1A ). SBC was 1.5 times more common in males than females. They were most frequently located at the duodenum (57.5%, n = 7860) where incidence almost tripled (0.24 to 0.63 per 100, 000), and less frequently at the jejunum (12.1%) and ileum (30.4%) where incidence approximately doubled (0.07 to 0.11 and 0.14 to 0.33 per 100, 000 respectively). The incidence in white patients was 1.5 times higher than black patients and 3 times higher than in Asian patients over the period 2001 to 2009 (Figure 1B ). SBC incidence was unchanged with respect to socio-economic status. Conclusion: The incidence of SBC in the UK has increased over the last two decades with little improvement in mortality rates. It is most common in males in their 6 th decade and in the proximal small intestine, which is in keeping with current literature. However, the higher incidence in white patients is in contrast to the geographical variation seen in both United States SBC and UK colorectal cancer data. A more comprehensive understanding of the natural history, environmental and genetic predisposition is needed to allow for potential patient stratification, more efficient diagnosis and treatment and thus improving its poor prognosis. Reference: 1 Ross et al . British Journal of Cancer . 1991;63:143–145 Disclosure of Interest: None Declared.